Adoptive Transfer of Immune Cells Into RAG2IL-2Rγ-Deficient Mice During Litomosoides sigmodontis Infection: A Novel Approach to Investigate Filarial-Specific Immune Responses - Wiszniewsky, Anna; Layland, Laura E.; Arndts, Kathrin; Wadephul, Lisa M.; Tamadaho, Ruth S. E.; Borrero-Wolff, Dennis; Chunda, Valerine C.; Kien, Chi Anizette; Hoerauf, Achim; Wanji, Samuel; Ritter, Manuel (Frontiers in Immunology, 2021)
Despite long-term mass drug administration programmes, approximately 220 million people are still infected with filariae in endemic regions. Several research studies have characterized host immune responses but a major obstacle for research on human filariae has been the inability to obtain adult worms which in turn has hindered analysis on infection kinetics and immune signalling. Although the Litomosoides sigmodontis filarial mouse model is well-established, the complex immunological mechanisms associated with filarial control and disease progression remain unclear and translation to human infections is difficult, especially since human filarial infections in rodents are limited. To overcome these obstacles, we performed adoptive immune cell transfer experiments into RAG2IL-2R-deficient C57BL/6 mice. These mice lack T, B and natural killer cells and are susceptible to infection with the human filaria Loa loa. In this study, we revealed a long-term release of L. sigmodontis offspring (microfilariae) in RAG2IL-2R-deficient C57BL/6 mice, which contrasts to C57BL/6 mice which normally eliminate the parasites before patency. We further showed that CD4+ T cells isolated from acute L. sigmodontis-infected C57BL/6 donor mice or mice that already cleared the infection were able to eliminate the parasite and prevent inflammation at the site of infection. In addition, the clearance of the parasites was associated with Th17 polarization of the CD4+ T cells. Consequently, adoptive transfer of immune cell subsets into RAG2IL-2R-deficient C57BL/6 mice will provide an optimal platform to decipher characteristics of distinct immune cells that are crucial for the immunity against rodent and human filarial infections and moreover, might be useful for preclinical research, especially about the efficacy of macrofilaricidal drugs.